Analysis The Role of School Culture in Shaping The Personality and Character of Students - Saryanto, Saryanto; Retnaningsih , Rahayu; Nofirman , Nofirman; Muhammadiah , Mas’ud; Yuniwati , Ika (Mudir : Jurnal Manajemen Pendidikan, 2023)
This research intends to analyze how well school culture affects kids' character development. The principal, curriculum area, class instructors, school staff, and a number of class pupils served as the research subjects in this study, which used a descriptive qualitative methodology. Observation, interviews, questionnaires, and documentation are all used as data gathering methods. Objectivity and triangulation are used in data validity assessments. The procedures of data reduction, data presentation, and conclusion drawing were used to examine the data. The findings demonstrated the value of school culture in one of schools in Indonesia, in primary school kids' character development. Students develop character, discipline, responsibility, civility, and a love of reading via school culture.